Semiotic Analysis of the Song Nasida Ria: Representation of Global Themes - Wahyudi, M. Firman; Lukman Fahmi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
The research entitled "Semiotic Analysis of the Song Nasida Ria: Representation of Global Themes" aims to describe the use of diction and the meaning contained in the lyrics of the song "Perdamaian". The data used in this research is one of the lyrics of Nasida Ria's song. This research uses a qualitative descriptive method, the qualitative research was carried out naturally, and was not manipulated by the author and the presence of a writer did not influence the object under study. The research was carried out by collecting data by listening and note-taking techniques. The data is collected in the form of text that has been carefully and carefully selected, which is then classified based on categories and recorded on a data card. The theory used includes the theory of Charles Morris's semiotic analysis. The results of the research entitled "Semiotic Analysis of the Song Nasida Ria: Representation of Global Themes have three parts, namely, first, semantic, discussing the meaning of the language in the song's lyrics, second, pragmatic, also to find out what is meant by the speech in the song's lyrics. And the three syntaxes discuss the language contained in the song so that we can see that there is a meaning or purpose that is intended in the song.